Short chain acyl-coenzyme A dehydrogenase (SCAD) deficiency. Immunochemical demonstration of molecular heterogeneity due to variant SCAD with differing stability. - Naito, E (1989)
Using a [35S]methionine labeling/immunoprecipitation technique, we have previously shown that cultured skin fibroblast from three patients with short chain acyl-CoA dehydrogenase (SCAD) deficiency each synthesize a normal-sized (41 kD) variant SCAD in an amount comparable to that of normal cells. In the current study, these same cell lines were reexamined with immunoblot analysis. In one cell line (YH2065) no SCAD protein was detectable. In the other two deficient cell lines, the amount of variant SCAD was similar to, or only slightly less than, normal. These results suggested that SCAD-YH2065 is labile. In the pulse-labeling experiments, labeled SCAD was readily detectable for at least 30 h in a normal control and two other SCAD-deficient cell lines. In contrast, the labeled SCAD band in YH2065 cells was barely detectable at 6 h and undetectable at 20 h. [35S]Methionine-labeling in the presence of rhodamine 6G demonstrated that SCAD-YH2065 was synthesized as a 44-kD precursor and imported normally into mitochondria, as were the normal SCAD and two other variant SCADs, excluding the possibility that SCAD-YH2065 is a truncated precursor that cannot be imported into mitochondria. These results indicate that the mutations responsible for SCAD deficiency are heterogeneous, and emphasize the importance of using both radiolabeling and immunoblotting when evaluating such genetic defects at the protein level.